Improvement of low temperature properties of jatropha-corn biodiesel blend with the addition of acrylic Co-polymer - Yun, H.M. (2013)
Inevitable low temperature properties is one of the major problems in commercialization of pure biodiesel. Increasing the usage of edible oil in biodiesel production creates the fuel versus food controversy. This paper involves the study of cold flow properties of edible and non-edible oil's biodiesel. Corn biodiesel and jatropha biodiesel are blended respectively. The blend ratio of corn methyl ester and jatropha methyl ester CME: JME (20:80) has the oxidative stability of 6.42 hours and cold filter plugging point value of -2 °C. An additive of acrylic co-polymer as the cold flow improver (CFI) reduced the CFPP value from -2 °C to -6 °C which results in better low temperature properties of corn-jatropha biodiesel blend. © (2013) Trans Tech Publications,Switzerland.